The impact of COVID-19 on obsessive-compulsive disorder - literature review - Grabowy, Paulina; Drożak, Martyna; Milanowska, Joanna (Journal of Education, Health and Sport, 2022)
Introduction: COVID-19 appeared in 2019. The first outbreak of the disease was in China, but it quickly spread to other countries, thus becoming a pandemic. This caused a tremendous stress and anxiety among the public, which also had a negative impact on their mental health. People with obsessive-compulsive disorder are especially sensitive in this respect. The aim of the study: Paying attention to the correlation between exacerbation of obsessive-compulsive symptoms and COVID-19 pandemic. Material and method: The research was done using PubMed and Google Scholar articles about the topic of: obsessive-compulsive disorder, COVID-19 pandemic, stress, mental health. Description of the state of knowledge: According to many studies, the COVID-19 pandemic has negatively impacted mental health of people with obsessive-compulsive disorder. The stress related to the pandemic resulting from concerns about being infected exacerbated the symptoms of obsessive-compulsive disorder. Doctors should pay close attention to OCD patients during pandemic and provide them with the treatment they need. Summary: Research results confirmed that COVID-19 contributed to the deterioration of symptoms in people with obsessive-compulsive disorder.